The Roles of CRM in the Telecommunication Industries in Singapore - CHONG, Yeng Keat (2007)
The shift of marketplace power fueled the heightened interest in relationship marketing and relationships management (CRM) since building customer trust and loyalty is crucial to the success of every company. Effective management of customers requires adequate of information and the technological advantage. Thus, telecommunications companies, like any other service companies, need to ensure that customer information are shared by all employees in order to have direct and immediate access whenever it is needed to enhance customer relationships management. While bigger organizations have the opportunity to leverage megabytes of data, better organizations are those that view each customer as a unique individual and mine the value of every customer transaction. These companies deployed CRM to gain clearer insight and more intimate understanding of customers' buying behaviors, thus helping to build an effective competitive advantage. Since many companies worldwide have adopted this approach, this study attempts to examine the role of CRM in telecommunications industry in order to identify its strengths and weaknesses in attracting and retaining customers in Singapore.